Impact of Basic Bath on Optical and Electrical Characteristics of Zinc Sulfide (ZnS) Thin Films - Tahir, Muhammad; Shah, Zaheer Hussain; Imran, Muhammad; Ramzan, Bilal; Riaz, Saira; Naseem, Shahzad (Scientific Inquiry and Review, 2024)
Zinc Sulfide (ZnS) thin films have attracted the research community because of their recognition in optoelectronic devices. An electroless, application-oriented, CBD (chemical bath deposition) method is typically applied for the deposition of ZnS thin films deposited on a glass substrate with pH 8. Deposition temperature is varied as 25℃, 50℃, 75℃, 100℃, and 125℃. In this study, ZnS thin films and X-ray diffraction (XRD) Variable Angle Spectroscopic Ellipsometry was used. XRD analysis confirmed the hexagonal structure of deposited ZnS thin films at all temperatures. Ellipsometric results showed high transmission (∼ 65%) in the visible region for thin films prepared with 50℃ deposition temperature and high refractive index at wavelength (λ = 550nm) ∼2.04. Variation in the direct band gap (Eg), 3.86–3.99 eV, was studied for synthesized thin films of ZnS. Improvement in optimizing the optical properties of ZnS thin films indicated an effective optoelectronic application.